Social Media Counseling as an Effective Channel for Youth Mental Health Support - Adaobi Jennifer Iloakasia; Chinwe Augustina Enwere (Greenation Publisher & Yayasan Global Research National, 2026)
Stress, anxiety and depression are among youth mental health issues that are on the rise all over the world, but access rates to traditional counselling services are still limited due to stigma, cost, and geographical issues. The study used quantitative survey design focusing on the youths in the state of Anambra in Nigeria. The virtual method was used to collect data through Google Forms, which ensured convenience and anonymity. A questionnaire in a structured form that included a four-point Likert scale was used to measure perceptions of social media counselling on dimensions of accessibility, confidentiality, professional involvement and mental health support. The questionnaire was confirmed by expert review and pilot test. Systematic compilation, coding and preparation of responses were done to undergo statistical analysis, with ethical concerns and privacy of the participants being considered in the research process. According to the study, female youths (69.7 ) were the majority in the sample, as males (30.3‛) followed, and 26.7 did not have gender data. There is a high perception of social media counselling as being extremely accessible and thought to involve youth engagement although there were low ratings of professional involvement and information reliability. Social media counselling is a proven method of supporting youth mental health, as it helps manage stress, anxiety, and personal challenges, as well as encourages emotional support. However, awareness-making is minimal. The correlation was found to be strong (r=0.664, p= <0.01) and showed that the more youths engage in social media counselling, the better their mental health outcomes were, which supports the idea that this intervention can be helpful to them. The results suggest that social media counselling is an accessible, flexible, and supportive source of mental health advice for youths, and thus it has the potential to supplement traditional services.